Transfer Efficiency and Triumph in Sports: An Experimental Study of the Italian Serie A - Erdem Delice, M.; Gerçek, Erda (Eracle. Journal of Sport and Social Sciences, 2018)
The analysis of the efficiency of professional football clubs in terms of on-field results has been widely debated in the sport economics literature. This paper illustrates a non-parametric analysis evaluating the efficiencies of transfers in Italian Serie A football clubs for the 2008-09 and 2017-18 seasons by constructing inputs of player transfers of football clubs and outputs in the manner of the clubs’ game success by using Data Envelopment Analysis (“DEA”), the most popular nonparametric model for estimating productive efficiency, first introduced by Farrell (1957). Our findings show that the Juventus Football Club managed to achieve efficiency on their transfer policies for these football seasons, while on the other hand transfers of Parma Football Club performed rather very inefficiently with regard to their game performance. Additionally, we conclude that teams that won the championship trophy, such as Juventus, Internazionale and AC Milan, had full efficiency in their player transfers at the beginning of the respective season.